Patients’ perceptions of care in a Type 1 hybrid effectiveness-implementation trial on intravenous iron for anaemia in pregnancy in Nigeria - Mobolanle Balogun; Opeyemi R. Akinajo; Rachel A. Thompson; Teniola Lawanson; Hameed Adelabu; Nadia A. Sam-Agudu; Bosede B. Afolabi (PLoS ONE, 2026)
Introduction Iron deficiency anaemia is a common cause of anaemia in pregnancy, which is highly prevalent in low-and middle-income countries (LMICs). Evidence from LMICs indicates that intravenous (IV) iron formulations such as ferric carboxymaltose (FCM) are safe and effective alternatives to oral iron, and there is emerging data on implementation strategies and outcomes. Client outcomes are important additional considerations for successful scale-up of new interventions. We assessed patient experiences and satisfaction among women receiving IV versus oral iron for anaemia in pregnancy in Nigeria. Methods This mixed-methods study was nested in a type 1 hybrid effectiveness-implementation trial that enrolled 1,056 pregnant women at 20–32 weeks gestational age. Participants were randomised to receive either FCM or oral ferrous sulphate (FS). Twenty-five percent of participants were sequentially sampled for interviewer-administered exit surveys and 66 women who received IV iron were purposively selected for in-depth interviews at last study visit. Quantitative data from the two treatment groups were evaluated using the Chi-squared test, while qualitative data were analysed thematically. Results We surveyed 252 women (128 treated with FCM and 124 with FS). Significantly higher proportions of the FCM (73.4%) versus FS group (57.3%) had positive perceptions of care (p = 0.007). Positive perceptions, experiences and satisfaction with FCM were buttressed by the qualitative findings, for reasons such as good communication and quality of provider care, single-dose administration, minimal side effects, positive health outcomes and not bearing treatment costs. Conclusion Participants in this IV versus oral iron trial had positive perceptions of FCM. These patient-reported findings support available evidence on service and implementation outcomes and further support IV iron scale up in LMIC settings. Future implementation research should further assess client outcomes under real-world conditions.